Activity of medicinal plants from Ghana against the parasitic gut protist Blastocystis. (4th November 2015) - Bremer Christensen, Charlotte; Soelberg, Jens; Stensvold, Christen R.; Jäger, Anna K.
Abstract: Ethnopharmacological relevance: The plants tested in this study were examples of plants historically used to treat or alleviate several types of stomach disorders manifested by e.g . stomachache, diarrhoea or dysentery. These plants have been consumed typically as a decoction, sometimes mixed with other flavourings. The aim of this study was to evaluate the anti- Blastocystis activity of 24 plant parts from 21 medicinal plants from Ghana. Materials and methods: The medicinal plants were collected in the Greater Accra region of Ghana. Every plant part was tested in three different extracts; an ethanolic, a warm, and a cold water extract, at a final concentration of 1 mg/mL for the initial screening, and in a range from 0.0156 to 1 mg/mL for determination of inhibitory concentrations. The obligate anaerobic parasitic gut protist Blastocystis (subtype 4) was used as a 48 h old subcultivated isolate in the final concentration of 10 6 cells/mL. Plant extracts inoculated with Blastocystis were incubated at 37 °C for 24 h and 48 h. Both MIC minimum inhibitory concentration (MIC90 ) assays and minimal lethal concentration (MLC) assays were performed after 24 h and 48 h. The half maximal inhibitory concentration (IC50 ) was derived after 24 h and 48 h. Antimicrobial activity was tested against two Gram-positive and two Gram-negative bacteria for all 24 plant parts at a final concentration of 1 mg/mL. Results: Screening of the 24 different plant parts showed significant anti- Blastocystis activity of six of the ethanolic extracts: Mallotus oppositifolius, IC50, 24 h 27.8 µg/mL; Vemonia colorata, IC50, 24 h 117.9 µg/mL; Zanthoxylum zanthoxyloides, cortex IC50, 24 h 255.6 µg/mL; Clausena anisata, IC50, 24 h 314.0 µg/mL; Z. zanthoxyloides, radix IC50, 24 h 335.7 µg/mL and Eythrina senegalensis, IC50, 24 h 527.6 µg/mL. The reference anti-protozoal agent metronidazole (MTZ) had an IC50, 24 h of 7.6 µg/mL. Only C. anisata showed antimicrobial activity at a concentration of 800 µg/mL. Conclusion: Six ethanolic plant extracts showed significant anti-parasitic activity against Blastocystis. M. oppositifolius showed nearly as good activity as the reference anti-protozoal drug MTZ. Historically, the active plants found in this study have been used against dysentery, diarrhoea or other stomach disorders. Nowadays they are not used specifically for dysentery, but they are being used as medicinal plants against various stomach disorders. Graphical abstract: